1999
DOI: 10.1007/bf02442139
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal concentrations in surficial sediments from Wadi El Natrun saline lakes, Egypt

Abstract: Abstract. Heavy metal concentrations of Wadi E1 Natrun saline lakes were investigated. Pb, Zn, Mn, Cu, Cd, Ni, Fe and A1 were measured in surficial sediments. The heavy metal concentrations largely indicate the influence of weathering of terrigenous sources on land. In comparison with the average in sedimentary rocks, the concentrations of the heavy metals studied are higher than the global average sandstone. This is also reflected in the high enrichment factors. The heavy metal concentration in lakes II and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Many saline lakes worldwide are shrinking at alarming rates, reducing waterbird habitat, leading to economic losses, and threatening human health [6]. There are few studies on metals in saline lake sediments [24,25]. Particularly, saline continental lakes are sensitive to metal pollution because sediments from hypersaline ecosystems are considered sinks and sources of trace elements [24].…”
Section: Saline Lakesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many saline lakes worldwide are shrinking at alarming rates, reducing waterbird habitat, leading to economic losses, and threatening human health [6]. There are few studies on metals in saline lake sediments [24,25]. Particularly, saline continental lakes are sensitive to metal pollution because sediments from hypersaline ecosystems are considered sinks and sources of trace elements [24].…”
Section: Saline Lakesmentioning
confidence: 99%
“…There are few studies on metals in saline lake sediments [24,25]. Particularly, saline continental lakes are sensitive to metal pollution because sediments from hypersaline ecosystems are considered sinks and sources of trace elements [24].…”
Section: Saline Lakesmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption of metals on sediments is surface area dependent, with the clay fraction providing the greatest potential for adsorption (Jickells and Knap, 1984). Taher and Soliman (1999) found enrichment of heavy metals in the fine silt and clay fraction in surficial sediments from Wadi El Natrun saline lakes. Mostafa et al (2004) found a robust relationship between the fine grained clays and Al content in Alexandria Harbor.…”
Section: Introductionmentioning
confidence: 97%
“…3 for As, Cr, Hg, Ni, Pb and Zn in surficial samples of the lagoons. Reference data were separated into three major groups, to account for different anthropogenic pressures and environmental settings: industrial/urban areas (Tanner et al, 2000;Zago et al, 2001;Berg et al, 2001;Bellucci et al, 2002;Bertolotto et al, 2003;Adamo et al, 2005;Ferraro et al, 2006;McCready et al, 2006;Marmolejo-Rodriguez et al, 2007;Harikumar and Nasir, 2010;Nikolaidis et al, 2010), coastal areas (Taher and Soliman, 1999;Dauvalter and Rognerud, 2001;Zabetoglou et al, 2002;Sericano et al, 2001;Preda and Cox, 2002;Bertolotto et al, 2003;Kishe and Machida, 2003;Cuong and Obbard, 2006;Farkas et al, 2007;Nobi et al, 2007;Romano et al, 2010) and lagoons (Bellucci et al, 2002). The values measured in Vietnamese lagoons are by far among the lowest (up to one order of magnitude) of the entire set for all elements considered, being lower but comparable to other coastal systems.…”
Section: Depositional Settings and Organic Matter Originmentioning
confidence: 99%